Effects of Dual-Site Anodal Transcranial Direct Current Stimulation on Attention, Decision-Making, and Working Memory during Sports Fatigue in Elite Soccer Athletes - Fengxue Qi; Na Zhang; Michael A. Nitsche; Longyan Yi; Yingqiu Zhang; Tian Yue (Journal of Integrative Neuroscience)
Background: Sports fatigue in soccer athletes has been shown to decrease neural activity, impairing cognitive function and negatively affecting motor performance. Transcranial direct current stimulation (tDCS) can alter cortical excitability, augment synaptic plasticity, and enhance cognitive function. However, its potential to ameliorate cognitive impairment during sports fatigue remains largely unexplored. This study investigated the effect of dual-site tDCS targeting the dorsolateral prefrontal cortex (DLPFC) or primary motor cortex (M1) on attention, decision-making, and working memory in elite soccer athletes during sports fatigue. Methods: Sports fatigue was induced in 23 (non-goalkeeper) elite soccer athletes, who then participated in three counterbalanced intervention sessions: dual-site tDCS over the M1, dual-site tDCS over the DLPFC, and sham tDCS. Following tDCS, participants completed the Stroop, Iowa Gambling, and 2-back tasks. Results: We found a significant improvement in Stroop task accuracy following dual-site anodal tDCS over the M1 compared with the sham intervention in the incongruent condition (p = 0.036). Net scores in the Iowa Gambling task during blocks 4 (p = 0.019) and 5 (p = 0.014) significantly decreased under dual-site tDCS targeting the DLPFC compared with the sham intervention. No differences in 2-back task performance were observed between sessions (all p > 0.05). Conclusions: We conclude that dual-site anodal tDCS applied to the M1 enhanced attention performance while tDCS targeting the DLPFC increased risk propensity in a decision-making task during sports fatigue in elite soccer athletes. However, dual-site anodal tDCS targeting either the M1 or DLPFC did not significantly influence working memory performance during sports fatigue in this population. These preliminary findings suggest that dual-site tDCS targeting the M1 has beneficial effects on attention performance, potentially informing future research on sports fatigue in athletes. Clinical Trial Registration: No: NCT06594978. Registered 09 September, 2024; https://clinicaltrials.gov/search?cond=NCT06594978.